Inheritance of the resistance to corn stunt - Silveira, Flávio Trevizoli; Moro, José Roberto; Silva, Herberte Pereira da; Oliveira, João Ademir de; Perecin, Dilermando (Pesquisa Agropecuaria Brasileira, 2009)
The objectives of this work were to determine the inheritance of resistance to corn stunt and determine the best resistance sources among the studied inbred lines. Diallel analysis and generation means were made for corn inbred lines. For the diallel analysis, twelve corn-inbred lines were crossed, in a partial diallel scheme. For the analyses of generation means, three resistant inbred lines and four susceptible ones were crossed, to obtain the F1, F2, RCPR and RCPS generations. The experiments were carried out in Jaboticabal, SP, Brazil. Corn sfunt incidence was evaluated at the phenological phase R3. Significant effects for CGC and CEC were obtained, which indicated that both additive and dominance effects were involved in corn expression of resistance to stunt. The analyses of generation means showed that few genes are involved in the resistance control, with predominant additive effects, which allows the selection of resistant genotypes. Lineages L02, L03 and L05 may be used as resistance sources in future hybrid combinations.